Course Sharing: An Interprofessional Education (IPE) Perspective - Anita Hazelwood; Jennifer B Lemoine (Academic Chairpersons Conference Proceedings, 2023)
This presentation will walk participants through the steps in developing interprofessional courses; identifying course offerings, exploring units interested in course sharing, soliciting administrative support, and balancing workloads for faculty. A case study describing the introduction of a legal and ethics course will be presented and results discussed.
Keywords: IPE; Trends; Interprofessional; Collaboration; Shared